An exploratory study examining the influence of the number of reading methods courses on pre-service and in-service teacher perceptions of ability to teach reading. Issue 2 (14th March 2016) - Clark, Sarah
Abstract : Teacher education programmes (TEPs) are left with limited research on how the coursework they provide influences the perceptions teachers have about their ability to teach young children how to read – especially over the long term. The purpose of this study was to compare how teacher candidates rate their ability to teach reading at the conclusion of their TEP, and then again after a year of teaching. The matched participants ( N  = 126) were elementary education teachers representing five TEPs in one US state. Results revealed that the number of reading methods courses provided does influence the perceptions of pre-service and in-service teachers. Teachers who had two reading methods courses compared with teachers who had only one reading methods course reported statistically significant higher scores at the pre-service stage and were able to maintain higher scores at the in-service stage. Implications of these findings are discussed.